Determination of the Liver Enzymes Level and Kidney Functions in Pregnant Women in the Second Trimester of Pregnancy at Different Age Groups - A. Al-Jowary, Suha (Iraqi Journal of Science, 2021)
The level of liver enzymes and kidney functions in pregnant women in the second trimester of pregnancy at different age groups was determined. This study is composed of fifty pregnant women in the second trimester of pregnancy and were classified into two subgroups; first group included twenty-five pregnant with an age between 22-30 years, a second group included twenty-five pregnant with an age 35-42 years. A control group included twenty-five non-pregnant, healthy women was also included. Blood samples were obtained from each group, centrifuged, serum was collected from each group to measure liver enzymes (AST, ALT and ALP) and kidney function tests (urea and creatinine) were measured using enzymatic kits. The results of present study illustrated significant elevation (P≤ 0.05) in AST and ALT means in the age group 35- 42 years, while there were no-significant differences in an age group 22- 30 compared with control healthy group. In addition, the ALP mean values are significantly increase(P≤0.05) in 22- 30 and 35- 42 years compared with non-pregnant women. The findings also demonstratedthat the means of blood urea is significantly declined (P≤0.05) in the age groups 22- 30 and 35- 42 years compared with healthy non-pregnant. This studyfoundsignificant decline(P≤0.05) in serum creatinine at an age group 22- 30 and significant increase(P≤0.05) in the other group (35- 42 years) compared with the control. The conclusion of the present study that hepatic and renal functions are more damaged in an age group 33- 42 years than an age group 22- 30 years through the values of parameters above. Therefore, pregnancy in the age 22- 30 years is more healthyfor both mother and fetus than an age 33- 42 years.